Pengaruh Model Problem Based Learning Berbantuan Media Genially Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Fisika Siswa SMA - Harirotul Lathifah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by Genially media on the critical thinking skills and physics learning outcomes of high school students on heat transfer material. This study uses a quantitative approach with a true experimental research type. The research design used is a posttest-only control group design. The research sample was determined using a cluster random sampling technique consisting of an experimental class and a control class. Data analysis was carried out using SPSS software version 26. The normality test was carried out using Shapiro-Wilk and showed that the data were not normally distributed, so the hypothesis testing was carried out using the nonparametric Mann-Whitney U test. The results of the analysis showed that students' critical thinking skills obtained a significance value (2-tailed) of 0.017 (<0.05), which means there is a significant difference between the experimental class and the control class. Meanwhile, student learning outcomes obtained a significance value (2-tailed) of 0.002 (<0.05), which also indicates a significant difference between the experimental class and the control class. Based on the research results, it can be concluded that the Problem-Based Learning (PBL) model, supported by Genially media, has an impact on high school students' critical thinking skills and physics learning outcomes in heat transfer.
Finalisasi 14 Juli 2026_Yudi
Keywords: Problem-Based Learning; Genially; critical thinking skills; learning outcomes; heat transfer